KNOWLEDGE MANAGEMENT STRATEGY TO IMPROVE QUALITY AND COST AT PT TOTAL BANGUN PERSADA TBK - Agustinus Ferry Setiawan (Jurnal Scientia, 2023)
Indonesia's construction industry should rise in 2023 as the COVID-19 epidemic improves. Indonesia's construction sector, especially the high-rise building market, would benefit from solid economic development in 2023. Despite better growth in 2023, high inflation, increasing interest rates, and industrial fragmentation still threaten the sector's stability. PT Total Bangun Persada Tbk faces tougher competition in this sector due to the macroeconomic condition. PT Total Bangun Persada Tbk, a customer-focused construction service firm, prioritizes product quality and after-sales service. The firm also takes consumer concerns seriously and studies them to improve. Recently, the corporation has challenged to deliver high-quality products for long-term sustainability consistently and the costs incurred from defects after handover from year to year relatively same. To ensure long-term viability and competitiveness, PT Total Bangun Persada Tbk will continue to improve the knowledge and skills of its employees. This is essential to the company's long-term viability and success. Additionally, the company must manage knowledge, disseminate it to employees, and incorporate it into the construction process. This would allow the business to raise its level of productivity, thereby lowering its overall costs while maintaining its ability to provide services of a consistently high quality. The purposes of this research are to identified knowledge gap and the critical knowledge to find knowledge management strategy and knowledge management initiatives to improve the knowledge management practices in order to support and solve the issues by improving the quality services delivered and reducing the cost.